2001
DOI: 10.1016/s0006-3495(01)76147-4
|View full text |Cite
|
Sign up to set email alerts
|

Arg615Cys Substitution in Pig Skeletal Ryanodine Receptors Increases Activation of Single Channels by a Segment of the Skeletal DHPR II-III Loop

Abstract: The effect of peptides, corresponding to sequences in the skeletal muscle dihydropyridine receptor II-III loop, on Ca(2+) release from sarcoplasmic reticulum (SR) and on ryanodine receptor (RyR) calcium release channels have been compared in preparations from normal and malignant hyperthermia (MH)-susceptible pigs. Peptide A (Thr(671)-Leu(690); 36 microM) enhanced the rate of Ca(2+) release from normal SR (SR(N)) and from SR of MH-susceptible muscle (SR(MH)) by 10 +/- 3.2 nmole/mg/min and 76 +/- 9.7 nmole/mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The greater increase in relative mean current at j40 mV ( Figure 5B) was due to the fact that the closed times were longer, and the frequency of events lower, in control activity at that potential than control activity at k40 mV. The effects of peptide A1(-R18) on single-channel parameters (a strong decrease in closed times and an increase in event frequency, with only a small increase in mean open time) were the same as the effects seen with peptide A1 [2,23]. The major difference between the peptides was in the magnitude of the effects, which was 2-10-fold greater with A1(-R18) than with A1.…”
Section: Enhanced A1(d-r18)-induced Activation Of Single Ryr Channelsmentioning
confidence: 73%
“…The greater increase in relative mean current at j40 mV ( Figure 5B) was due to the fact that the closed times were longer, and the frequency of events lower, in control activity at that potential than control activity at k40 mV. The effects of peptide A1(-R18) on single-channel parameters (a strong decrease in closed times and an increase in event frequency, with only a small increase in mean open time) were the same as the effects seen with peptide A1 [2,23]. The major difference between the peptides was in the magnitude of the effects, which was 2-10-fold greater with A1(-R18) than with A1.…”
Section: Enhanced A1(d-r18)-induced Activation Of Single Ryr Channelsmentioning
confidence: 73%
“…Ribba et al [25] showed that the Arg552Cys mutation in the von Willebrand factor resulted in abnormal folding and loss of function resulting in type 2A-like phenotype of von Willebrand disease. The Arg615Cys substitution in ryanodine receptors increases calcium release in malignant hyperthermia-susceptible pigs [9].…”
Section: Discussionmentioning
confidence: 99%
“…First, it increases transient activity in skeletal RyRs with high affinity (Ն10 nM) and releases Ca 2ϩ from skeletal SR (5,6,10,(12)(13)(14)(15)(16)(17)(18). Ca 2ϩ -induced Ca 2ϩ release from cardiac SR is enhanced by the peptide and cardiac RyRs activated at sub-activating cis [Ca 2ϩ ].…”
Section: Discussionmentioning
confidence: 99%
“…3 The second action is a voltage-independent inhibition, seen specifically with the modified A1-R18D at Ն10 nM in skeletal and cardiac RyRs with 100 M cis Ca 2ϩ . 3 The native peptide A is less active with 100 M cis Ca 2ϩ than with lower [Ca 2ϩ ] (12,17). Because peptide structure is not Ca 2ϩ -dependent, 3 this inhibition raises the possibility either that there is a separate inhibitory site or the activation site can become inhibitory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation